The development of cisplatin resistance in neuroblastoma is accompanied by epithelial to mesenchymal transition in vitro. Issue 2 (10th August 2015) - Piskareva, Olga; Harvey, Harry; Nolan, John; Conlon, Ross; Alcock, Leah; Buckley, Patrick; Dowling, Paul; O'Sullivan, Finbarr; Bray, Isabella; Stallings, Raymond L.
Highlights Cisplatin induced cross resistance to temozolomide, etoposide and irinotecan. Proteomic profiling of three cisplatin resistant neuroblastoma cell sublines. Altered proteins had cellular growth and proliferation, cell death and survival classifications. Increased migration of SK-N-ASCis24 correlates with elevated levels of MYH9 and ACTN4. EMT and increased cell migration are associated with drug resistance in SK-N-ASCis24.